Temporal prepositions in German and their equivalents in Turkish Temporale prapositionen im Deutschen und ihre wiedergabemöglichkiten im Türkischen - Aygün, Mehmet
Fırat Üniversitesi Sosyal Bilimler Dergisi, 13-2 (Temmuz, 2003) 91-114 ss.